Anomalias gravitacionais em duas dimensões via regularização implícita - Leonardo Antonio Mendes de Souza (2005)
In this work we study the gravitational anomalies (Einstein anomaly andWeyl anomaly) in two dimensions through the method of implicit regularization (RI). We present a brief review on the minimal mathematical tools to treat the problem. After that, we use the method of RI to calculate the amplitude relative to the problem, and consequently the Ward identities. We show that our results do not depend on the subtraction point of the divergent integrals and that two regularization dependend parameters remain in the end of the calculations. The numeric values of these parameters are stipulated through symmetry arguments. Finally we show the final results about the Einstein and Weyl anomalies.